Paradigmatic Dynamics in Ulum al-Hadith: Classical Authentication Methods and Modern Historical-Critical Debates - Muhajirah Binti Jamaluddin; Imamul Authon Nur (Al-Mu'tabar, 2026)
This article examines the paradigm transformation in Ulūm al-Ḥadīṡ through debates on hadith authenticity in classical and contemporary Islamic scholarship. It aims to formulate an integrative epistemological framework that bridges classical hadith criticism and modern historical-critical approaches. The novelty of this study lies in proposing a conceptual synthesis between naqd al-sanad, naqd al-matn, and socio-historical analysis as complementary approaches in assessing hadith authenticity. This study applies qualitative library research using textual analysis of selected classical hadith manuals and contemporary academic works on hadith criticism. Primary data include classical works of muṣṭalaḥ al-ḥadīṡ and modern scholarly studies, while secondary data consist of interdisciplinary literature on Islamic epistemology and authenticity discourse. Data were analyzed using descriptive, comparative, and historical approaches. The findings indicate that the classical paradigm emphasizes sanad continuity, narrator reliability, and textual consistency, whereas modern approaches focus on socio-historical reconstruction and contextual interpretation. The study identifies a possible convergence in which classical criticism provides methodological rigor, while modern analysis contributes interpretive depth. However, integration must remain epistemologically selective to prevent weakening the normative authority of hadith. Therefore, this study proposes an integrative framework that places classical methodology as the epistemic foundation while adopting critical contextual analysis. This model strengthens the relevance and epistemological resilience of Ulūm al-Ḥadīṡ in contemporary scholarship.